2017
DOI: 10.1097/yct.0000000000000401
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation in Substance Use Disorders

Abstract: In light of these data, it is premature to conclude that tDCS over the dorsolateral prefrontal cortex is a very efficient technique in reducing craving. Small sample size, different stimulation protocols, and study duration were the main limitations. However, the efficacy of tDCS in treating SUDs requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 39 publications
0
52
0
Order By: Relevance
“…The DLPFC findings are particularly important given the role of this region in cognitive control and other executive functions that contribute to drinking decisions (Niendam et al 2012). The DLPFC is also commonly targeted via neuromodulation interventions using non-invasive brain stimulation techniques (e.g., Boggio et al, 2008;Coles, Kozak, & George, 2018;Lupi et al, 2017;Mishra, Nizamie, Das, & Praharaj, 2010) and cognitive interventions such as executive function or working memory training (Duda and Sweet, In Press;Olesen, Westerberg and Klingberg, 2004;Takeuchi et al, 2011). Furthermore, by demonstrating that no regions are associated with alcohol use beyond their shared associations with the DLPFC, the current study highlights the importance of DLPFC in understanding how alcohol use is linked with the brain.…”
Section: Discussionmentioning
confidence: 99%
“…The DLPFC findings are particularly important given the role of this region in cognitive control and other executive functions that contribute to drinking decisions (Niendam et al 2012). The DLPFC is also commonly targeted via neuromodulation interventions using non-invasive brain stimulation techniques (e.g., Boggio et al, 2008;Coles, Kozak, & George, 2018;Lupi et al, 2017;Mishra, Nizamie, Das, & Praharaj, 2010) and cognitive interventions such as executive function or working memory training (Duda and Sweet, In Press;Olesen, Westerberg and Klingberg, 2004;Takeuchi et al, 2011). Furthermore, by demonstrating that no regions are associated with alcohol use beyond their shared associations with the DLPFC, the current study highlights the importance of DLPFC in understanding how alcohol use is linked with the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Growing attention has been given to noninvasive brain stimulation techniques in addictive disorders as novel therapeutic modalities. Noninvasive brain stimulation techniques of repeated transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS) have demonstrated significant effects in controlling of substance or food cravings [87,88].…”
Section: Neuromodulationmentioning
confidence: 99%
“…Considerable evidence has demonstrated that modulating the activities of addiction-related brain areas is a promising strategy to control drug use and relapse [75]. Although there are various ways to modulate the activity of a specific brain area, such as random noise stimulation, ultrasound stimulation, electoral stimulation, and magnetic stimulation, recent research has been focusing on the latter two [76,77]. Transcranial magnetic stimulation (TMS) and transcranial direct current stimulation (tDCS) are two of the best-studied approaches for treating drug addiction and other mental disorders [76][77][78][79].…”
Section: Brain Stimulationmentioning
confidence: 99%
“…Although there are various ways to modulate the activity of a specific brain area, such as random noise stimulation, ultrasound stimulation, electoral stimulation, and magnetic stimulation, recent research has been focusing on the latter two [76,77]. Transcranial magnetic stimulation (TMS) and transcranial direct current stimulation (tDCS) are two of the best-studied approaches for treating drug addiction and other mental disorders [76][77][78][79]. Studies have shown that stimulating dorsal lateral PFC by TMS and tDCS were effective to reduce craving, improve cognition, and ameliorate the mood states in subjects using major drugs of abuse [76,80].…”
Section: Brain Stimulationmentioning
confidence: 99%
See 1 more Smart Citation